Looking back, looking forward: changes in the scope of the subject ‘animal welfare' within the World Organisation for Animal Health - Keeling, L J (Revue scientifique et technique (International Office of Epizootics), 2024)
Over the past few decades, the scope of animal welfare has expanded within the World Organisation for Animal Health (WOAH). This article takes as its starting point the first issue of the Scientific and Technical Review dedicated to the subject in 1994, and compares it to the second of 2005, and to the situation today, almost 20 years later. Changes are grouped into three main areas. The first is the consolidation of animal welfare work within WOAH and the acceptance of it as a subject in its own right, linked to - but nevertheless separate from - animal health. The second is the broadening of the subject's scope from being mainly concerned with farm animal welfare to encompassing all categories of animals, domesticated and wild. The third is the increased contextualisation of animal welfare to account for different regional attitudes and needs around the globe. Changes in the scope of the subject of animal welfare within WOAH reflect the increase in research in the area and demonstrate that animal welfare is becoming integrated into other complex areas, such as sustainable development. The final part of this article looks forward, speculating on roles that WOAH might play in the future in the area of animal welfare.